The Defining Elements of the Concept of Taxable Person under EU Law – Critical Appraisal with Special Reference to the Polish Concept of VAT Taxpayer - Wojciech MARUCHIN (Communications of International Proceedings, 2021)
The analysis of the EU law and the case-law of the Court of Justice of the European Union (CJEU) resulted in the emergence of the essential defining characteristics of taxable persons under EU value added tax (VAT) rules. They were the starting point for conducting comparative tax law research in the context of tax harmonization in the European Union, which resulted in the formulation of guidelines for the Polish legislator. These guidelines arise from a critical appraisal of certain elements of the concept of a taxable person under EU VAT rules. They were formulated after the assessment of Polish statutory regulations in view of the EU law, legal academic literature, and the judgments of both the CJEU and the Supreme Administrative Court of Poland (SAC).
Keywords: VAT; Impact of EU law on Polish law; VAT taxable person; VAT taxable person in Polish law; CJEU case-law; VAT taxable person in the EU; economic activity and VAT; implementation of EU law into Polish law.